Vaccinations through the mother's eyes - Natalia Alicja Świątoniowska; Anna Rozensztrauch (Kazimierz Wielki University, 2017)
Introduction. Mortality rate associated with infectious diseases has substantially decreased nowadays. This fact combined with negative perception of vaccination in mass media is becoming influential factor for parent when making the decision whether to vaccinate or not. Aim. This study aimed to assess parent's knowledge about child vaccinations Material and methods. The study was conducted between 102 mothers aged 28,6 ± 4,3. The research tool was a questionnaire of authors own design. Results. 85,3%  of mothers declared to support vaccination. Mothers living in a city more frequently agreed that vaccination could harm the child (25.8% vs. 8.3%, p <0.05) than mothers living in a village. Younger mother more often declared that they are vaccination supporters than older (p <0.05). 60.8% of surveyed mothers said that it is important to vaccinate the child with the recommended vaccinations. Mothers with higher educations and medical professions more often immunized their children with recommended vaccination.